Factor Analysis for the Questionnaire Investigation on the Needs at Yoshiwara Shopping Street in Fuji City - Suzuki, Daisuke; Okubo, Akane; Higuchi, Yuki; Takeyasu, Kazuhiro (Archives of Business Research, 2018)
Shopping streets at local city in Japan became old and are generally declining. In this paper, we handle the area rebirth and/or regional revitalization of shopping street. We focus on Fuji city in Japan. Four big festivals are held at Fuji city (two for Fuji Shopping Street Town and two for Yoshiwara Shopping Street Town). Many people visit these festivals including residents in that area. Therefore a questionnaire investigation to the residents and visitors is conducted during these periods in order to clarify residents and visitors’ needs for the shopping street, and utilize them to the plan building of the area rebirth and/or regional revitalization of shopping street. There is a big difference between Fuji Shopping Street Town and Yoshiwara Shopping Street Town. Therefore we focus Yoshiwara Shopping Street in this paper. These are analyzed by using Factor Analysis and Cluster Analysis. These are utilized for constructing a much more effective and useful plan building. We have obtained fruitful results. To confirm the findings by utilizing the new consecutive visiting records would be the future works to be investigated.